1979
DOI: 10.1287/opre.27.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Shortest-Route Methods: 1. Reaching, Pruning, and Buckets

Abstract: We present a new family of shortest-route methods, which reduce an upper bound on running time, and make empirical comparisons for a certain class of networks. These methods also allow for exploitation of structure by pruning arcs and/or nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
3

Year Published

1982
1982
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(66 citation statements)
references
References 18 publications
0
63
0
3
Order By: Relevance
“…Therefore, subsequent approaches have been designed to avoid the sorting complexity; they identified label-setting criteria that allow to scan nodes in nonsorted order. Dinitz [16] and Denardo and Fox [10] observed the following:…”
Section: Advanced Label-setting Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, subsequent approaches have been designed to avoid the sorting complexity; they identified label-setting criteria that allow to scan nodes in nonsorted order. Dinitz [16] and Denardo and Fox [10] observed the following:…”
Section: Advanced Label-setting Methodsmentioning
confidence: 99%
“…Hence, at first glance, label-setting algorithms seem to be the better choice. However, several independent case studies [6,10,13,28,29,44,50,70] showed that SSSP implementations of label-correcting approaches frequently outperform labelsetting algorithms. Thus, worst-case analysis sometimes fails to bring out the advantages of algorithms that perform well in practice.…”
Section: Worst-case Versus Average-case Analysismentioning
confidence: 99%
See 3 more Smart Citations